Análise acústica ou de oitiva? Contribuições para o estudo da palatização em Sergipe - Silva, Lucas Santos (2021)
Palatalization, as in tia/ʧia or dia/ʤia (aunt and day, respectively) configure themselves a dialectal marker in Brazilian Portuguese, and it has been emerging in Sergipano’s speech (SOUZA NETO, 2014 [2008]; SOUZA, 2016; CORRÊA, 2019). Contributing towards the description of palatalization in Sergipe and also considering that phonological processes in speech may be transferred to reading (PINHEIRO et al., 2017, SOUZA; SILVA; ARAÚJO JÚNIOR, 2020; FREITAG, 2020c), our general objective is to examine acoustic characteristics the palatalization of /t/ and /d/ in the reading aloud of students from different geographical profile at the Federal University of Sergipe (UFS), describing the realizations in three categories: alveolar stop [t, d], aspirated alveolar stop and alveolo-palatal[ʧ, ʤ]. As a theoretical framework, we base ourselves on the perspectives of sociophonetics (FOULKES et al., 2010; GONÇALVES; BRESCANCINI, 2017; THOMAS, 2010; DI PAOLO; YAGER-DROR, 2011),), an area that puts on the threshold as areas of Sociolinguistics and Phonetics. As a method, our corpus is composed of 36 recordings of a reading aloud of Vida de Cinema, by Érico Veríssimo (2019), performed by undergraduate students at UFS, Professor José Aloísio de Campos campus (São Cristóvão, SE), stratified into three commutes according to the region where they are from: I) residents of Aracaju metropolitan area (born and raised there); II) residents from the countryside (born and raised there) who commutes to study at the university; III) students born and raised in the countryside but who moved to the state capital because of the university. The acoustic categorization was analyzed at PRAAT (BOERSMA; WEENINK, 2017). From 831 data, three analyses were performed: (I) categoric analysis (comparing spontaneous speech [CORRÊA, 2019] to hearing categorization, and reading aloud data to acoustic categorization); (II) ternary analysis (description of the phenomenon into three levels - alveolar stops, aspirated alveolar stops, and alveolo-palatals); and (III) acoustic analysis (used to analyze the duration of initial voicing – VOT – in the three analyzed levels). In the categorical analysis, we observed higher occurrence rates of palatalization in reading aloud (48.98%) than in speech (12.75%), a result associated with the acoustic criteria for the identification of the phenomenon, the prestige of palatalization in the community, and the fact that the reading aloud task is highly monitored and conscious by the students. In relation to the ternary analysis, the results reveal that the production of aspirated alveolar stops and alveolopalatals initially emerge in the university students from Aracaju and newcomers to UFS, and the contexts that favored this emergency are: alveolo-palatal fricatives (in preceding contexts), oral vowels (following contexts), stressed and post-tonic word-final syllables, and voiceless sounds, following the tendency of previous studies (BARBOZA, 2013; SOUZA NETO, 2014 [2008]; SOUZA, 2016; SILVA FILHO, 2018; CORRÊA, 2019). In relation to the acoustic analysis, the means of VOT for the analyzed realizations were of 31.5ms for alveolar stops, 50.7 ms for aspirated alveolar stops, and 80.0 ms for alveolo-palatals with statistically significant differences when associated with the dialectal region of the student, sex/gender, following context, and tone. With the acoustic analysis proposition, the results signalize an advanced stage for the consolidation of the alveolo-palatal realizations and the effects of the commuting, the academic environment, and the specific phonotactic contexts in the emergency of linguistic uses. We highlight the limitations of the sample, mostly regarding the asymmetry of the linguistic contexts analyzed. The implementation of more paired contexts may widen the explanatory power of emergency in the palatalization in Sergipe.